A process evaluation of a peer education project to improve mental health literacy in secondary school students: study protocol - Emily Widnall; Steve Dodd; Ruth Simmonds; Helen Bohan; Abigail Russell; Mark Limmer; Judi Kidger (BMC, 2021)
Abstract Background Emotional disorders in young people are increasing but studies have found that this age group do not always recognise the signs and symptoms of mental health problems in themselves or others. The Mental Health Foundation's school-based Peer Education Project (PEP) has the potential to improve young people's understanding of their own mental health at a critical developmental stage (early adolescence) using a peer teaching method. This study is a process evaluation to understand: the mechanisms through which PEP might improve young people's mental health literacy, any challenges with delivery, how the project can be embedded within wider school life and how it can be improved to be of most benefit to the widest number of young people. We will also validate a bespoke mental health literacy questionnaire, and test the feasibility of using it to measure outcomes in preparation for a future study evaluating effectiveness. Methods All schools recruited to the study will receive the PEP intervention. The process evaluation will be informed by realist evaluation approaches to build understanding regarding key mechanisms of change and the impact of different school contexts. The evaluation will test and revise an existing intervention logic model which has been developed in partnership with the Mental Health Foundation. Process evaluation data will be collected from newly recruited schools (n = 4) as well as current PEP user schools (n = 2) including training and lesson delivery observations, staff interviews and student focus groups. Baseline and follow-up data will be collected in all newly recruited intervention schools (n = 4) from all students in Year 7/8 (who receive the PEP) and recruited peer educators in Year 12 via a self-report survey. Discussion This study will enable us to refine the logic model underpinning the peer education project and identify areas of the intervention that can be improved. Findings will also inform the design of a future effectiveness study which will test out the extent to which PEP improves mental health literacy.